Energy and exergy utilization efficiencies and emission performance of Canadian transportation sector, 1990-2035 - Motasemi, F.; Afzal, M.T.; Salema, A.A.; Moghavvemi, M.; Shekarchian, M.; Zarifi, F.; Mohsin, R. (Elsevier, 2014)
Transportation sector of Canada is the second largest energy consuming sector which accounts for 30% of the total energy consumption of the country in 2009. The purpose of this work was to analyze the energy, exergy, and emission performance for four different modes of transport (road, air, rail, and marine) from the year 1990-2035. For historical period, the estimated overall energy efficiency ranges from 22.41% (1991) to 22.55% (2006) with a mean of 22.48±0.07% and the overall exergy efficiency ranges from 21.61% (2001) to 21.87 (2006) with a mean of 21.74±0.13%. Energy and exergy efficiencies may reach 20.95% and 20.97% in the year 2035 respectively based on the forecasted data. In comparison with other countries, we found that in the year 2000 the overall energy and exergy efficiencies for Canadian transportation sector were higher than Jordan, China, Norway, and Saudi Arabia but lower than Turkey and Malaysia. Between the year 1990-2009, the highest amount of emission produced in each subsector was: road CO2 (80%), NOx (72%), and CO (carbon monoxide) (96%); air SO2 (86%); rail NOx (6%) and marine NOx (7%). The road subsector produced the highest amount of emissions.